(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Microbial natural products have long served as a valuable source of lead moieties for the discovery and development of new therapeutic agents. Microorganisms, including bacteria, fungi, and actinomycetes, produce structurally diverse secondary metabolites with significant biological activities, such as antibacterial, antifungal, antiviral, anticancer, and immunosuppressive properties. These bioactive molecules continue to play a crucial role in modern drug discovery by providing novel chemical scaffolds for the development of safer and more effective medicines. The increasing emergence of antimicrobial resistance and complex diseases has renewed interest in exploring microbial biodiversity for innovative lead compounds. Advanced cultivation techniques, genome mining, metagenomics, and synthetic biology have expanded the identification of previously inaccessible microbial metabolites. Chemical characterization of these natural products employs spectroscopic and spectrometric techniques including nuclear magnetic resonance (NMR), mass spectrometry (MS), infrared (IR), and ultraviolet-visible (UV-Vis) spectroscopy for structural elucidation. Analytical methods such as high-performance liquid chromatography (HPLC), gas chromatography–mass spectrometry (GC–MS), liquid chromatography–mass spectrometry (LC–MS), and capillary electrophoresis are widely used for separation, identification, quantification, and quality assessment of microbial metabolites. These techniques ensure the purity, stability, and reproducibility of lead compounds during pharmaceutical development. Integration of microbial biotechnology with modern analytical chemistry accelerates the discovery of promising drug candidates and facilitates their translation into clinically useful medicines. This overview highlights the significance of microbial natural products as lead moieties and emphasizes the importance of chemical characterization and analytical evaluation in advancing pharmaceutical research. Continued exploration of microbial resources is expected to contribute substantially to future drug discovery and the development of innovative therapeutics.